Framework molecular orbital models to show hybridization of atomic orbitals and isomerism - Pamplona, Buena S. 1940- (1970)
The objective of the study is to make framework molecular orbital models to show hybridization of atomic orbitals and isomerism. The study introduces the use of scaled, skeleton models of molecules as teaching devices to help teachers impart knowledge about structural chemistry with clarity.
Thesis (M.A.T.Chemistry)--University of the Philippines, Diliman.
Keywords: Molecular -- Models; Molecular orbitals